Kemampuan Berpikir Kritis Matematis Siswa Berdasarkan Efikasi Diri Pada Materi Bangun Ruang Sisi Datar - Dinda Nuraini; Rika Sukmawati; Sigit Raharjo; Shinta Aristy (Jurnal PEKA (Pendidikan Matematika), 2025)
This research aims to examine students' mathematical critical thinking abilities based on self-efficacy in flat-sided geometric material and students are expected to be able to have self-confidence in analyzing and solving problems critically. The research was conducted at Kafah Unggul Islamic High School, Tangerang City, with research subjects selected from 6 students from 14 class X Science students. The method used in this research is descriptive qualitative. The data analysis technique obtained through filling out a questionnaire regarding self-efficacy was analyzed using low, medium and high criteria and continued with a written test in the form of description questions with flat-sided geometric material and interviews. Based on the research results, it can be seen that the category level of students who have high self-efficacy is 25%. The largest category is 58.33% with moderate self-efficacy and the smallest is 16.66% in the low self-efficacy category which is caused by several factors, such as experiencing difficulties when analyzing and determining the formula to use according to the question.